Awareness of HIV/AIDS and other sexually transmitted infections among the Montenegrin seafarers - Jovićević, Ljiljana R; Parlić, Milan; Stevanović, Jasmina; Novaković, Tatjana R; Barjaktarović-Labović, Snežana; Milić, Marija (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Human immunodeficiency virus (HIV) continues to be a major global public health issue having claimed more than 35 million lives so far. Seafarers belong to a group of migrant workers whose working and living conditions are confined for a long time. Their way of life put them at a high risk of HIV infection and other sexually transmitted infections (STIs). The aim of this study was to assess the level of knowledge about HIV and other STIs among Montenegrin sailors. Methods. A research was carried out from October 2014 to April 2015 as a cross-sectional study. The research included 543 examinees. A research instrument was a particularly structured closed-type questionnaire created by the Joint United Nations Programme on HIV/acquired immune deficiency syndrome (AIDS) (UNAIDS) and used in international and national researches. For data analysis, we used the SPSS for Windows 20.0. Results. The result that only 42.9% of the examinees knew that HIV and STI transmission could be prevented by a proper and frequent use of condoms was alarming. More than a third of the examinees (38.9%) were aware of the fact that HIV could be transmitted by having sexual intercourse with a person who looked healthy, while 25.6% of them thought that HIV could not be transmitted in this way. Considering the level of education, there was a statistically significant difference related to the awareness of HIV transmission by sharing a meal with a person was HIV positive (p = 0.001). There was also found a statistically significant difference related to the awareness of the examinees about HIV transmission by using public toilets (p = 0.004). Conclusion. The results of this research showed that beside the fact that awareness level of HIV and STIs among the sailors was heightened in comparison to 2008, the level of awareness is still not satisfactory.
Keywords: hiv infections; attitude to health; humans; military personnel; surveys and questionnaires